(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
The article describes the pedagogical and psychological features of the development of the culture of information consumption in the global society. Also, the authors’ scientific analysis on the development of the culture of information consumption among future teachers is presented